Behavioral and social predictors of COVID-19 vaccine uptake among persons with disabilities in Kenya - Muchangi, Josphat Martin; Moraro, Rogers; Omogi, Jarim; Alasmari, Abrar; Simiyu, Sheillah; Bolio, Ana; Kanyangi, Lennah; Mwema, Rehema; Bukania, Rose; Kosgei, Sarah (Frontiers in Public Health, 2024)
Access and uptake of COVID-19 vaccine by persons with disabilities remains largely unknown in low-and middle-income countries, despite the unique barriers they face, their special vulnerabilities and higher risk to severe outcomes. We aimed to identify behavioral and social predictors of COVID-19 uptake among persons with disability in Kenya. A convergent parallel mixed method study design was conducted among 792 persons with disability in four regions (counties) in Kenya. Purposive sampling was used to identify the respondents from the National Council for Persons with Disabilities Registration database. Quantitative data were analyzed using STATA statistical analysis software (version 14). Chi-square (X2) and Fisher's exact tests were used to test for differences in categorical variables; and multivariate regression analysis done to ascertain the factors that influence the uptake of COVID-19 among persons with disabilities in Kenya. Qualitative data from 7 Focus Group Discussions and 4 Key Informant Interviews were transcribed and themes developed using the Behavioral and Social Drivers of vaccination framework by the World Health Organization. Approximately 59% of persons with disabilities reported to be fully vaccinated with significant disparities noted among those with cognition (34.2%) and self-care (36.6%) impairments. Key predictors of vaccine uptake included confidence in vaccine benefits (Odds ratio [OR]; 11.3, 95% CI[5.2–24.2]), health worker recommendation (OR; 2.6 [1.8–3.7]), employment (OR; 2.1 [1.4–3.1]), perceived risk (OR; 2.0 [1.3–3.1]), age 18–24 years (OR; 0.18 [0.09–0.36]), and rural area of residence (OR; 0.48 [0.29–0.79]). The primary reasons for low uptake included perceived negative vaccine effects and lack of adequate information. Qualitative findings revealed unique motivations for vaccination among persons with disabilities (PWDs), including safeguarding against risks from assistive devices and the influence of political leaders. Barriers included perceived vaccine effects, transportation challenges, and limited access to trusted information, highlighting the need for targeted sensitization, improved healthcare worker engagement, and collaboration with PWD organizations. Subsequent vaccination deployments should map and reach people in all disability domains through relevant institutions of PWDs and localized vaccination campaigns. Related communication strategies should leverage the credibility and trust in health workers and behavior change techniques that inspire confidence in vaccines to improve vaccine uptake.